IFC Annual Report 2009 : Creating Opportunity Where It's Needed Most, Volume 2. Financials, Projects, and Portfolio - International Finance Corporation (Washington, DC: World Bank, 2012)
International Finance Corporation (IFC) is an international organization, established in 1956, to further economic growth in its developing member countries by promoting private sector development. IFC's principal investment products are loans and equity investments, with smaller debt securities and guarantee portfolios. IFC also plays a catalytic role in mobilizing additional funding from other investors and lenders, either through co financing or through loan participations, underwritings, and guarantees. In addition to project finance, corporate lending and resource mobilization, IFC offers an array of financial products and advisory services to private businesses in the developing world to increase their chances of success. It also advises governments on how to create an environment hospitable to the growth of private enterprise and foreign investment. IFC raises virtually all of the funds for its lending activities through the issuance of debt obligations in the international capital markets, while maintaining a small borrowing window with International Bank for Reconstruction and Development (IBRD). The management discussion and analysis contains forward looking statements which may be identified by such terms as 'anticipates,' 'believes,' 'expects,' 'intends,' 'plans' or words of similar meaning. Such statements involve a number of assumptions and estimates that are based on current expectations, which are subject to risks and uncertainties beyond IFC's control. Consequently, actual future results could differ materially from those currently anticipated.